Effectiveness and cost-efficacy of diuretics home administration via peripherally inserted central venous catheter in patients with end-stage heart failure. (15th October 2022) - Godino, Cosmo; Scotti, Andrea; Marengo, Alessandra; Battini, Ivana; Brambilla, Paola; Stucchi, Silvia; Slavich, Massimo; Salerno, Anna; Fragasso, Gabriele; Margonato, Alberto
Abstract : Background: End-stage heart failure (ESHF) is characterized by severe cardiac dysfunction with persistent disabling symptoms and recurrent acute decompensated heart failure (ADHF), despite guideline-directed medical therapy. The aim of this study was to evaluate the efficacy and safety of intravenous diuretics administration at home through a peripherally inserted central venous catheter (PICC) in ESHF patients. Methods and results: Forty-one ESHF patients received PICC implantation for intravenous diuretic administration at home. The primary efficacy endpoint was the patient-level number of HF hospitalizations in the short (1– 3 months), medium (six months), and long term (1 year), before and after PICC implantation. Pre- and post-PICC ADHF-free days were also evaluated as co-primary endpoint. Secondary endpoints comprised changes in clinical, laboratory and echocardiographic parameters, and device safety. A cost-effectiveness analysis was performed to estimate the economic impact of using PICC. For each time frame analyzed, a significant reduction in the number of hospitalizations due to ADHF was observed, resulting in a significant increase in ADHF-free days (71 ± 44 vs. 163 ± 136, p = 0.003). In matched patients' analysis, significant decrease in body weight (68 ± 16 kg vs. 63 ± 10 kg, p = 0.041) and mitral regurgitation grade 3/4 (55% vs. 18%, p < 0.001) were also observed. Freedom from PICC-related complications was observed in 61% of patients. A significant reduction in overall ADHF-hospitalizations cost was observed. Conclusions: This proof-of-concept study demonstrates the effectiveness and safety of home administration of intravenous diuretic therapy via PICC in ESHF patients. This palliative cost-effective strategy can be taken in consideration for selected end-stage patients no longer responsive to conventional therapies. Highlights : The use of peripherally inserted central venous catheters (PICC) for home administration of intravenous diuretic therapy in patients with end-stage heart failure (ESHF) is safe, effective, and cost-efficient. The adoption of PICC for diuretic administration may constitute a valid palliative treatment strategy for patients with ESHF. The PICC device can efficiently deliver diuretics bypassing the oral diuretic resistance mechanism and represents an effective solution for home-based patient care.